2007
DOI: 10.1063/1.2472189
|View full text |Cite
|
Sign up to set email alerts
|

Electrical property improvements of high-k gate oxide by in situ nitrogen incorporation during atomic layer deposition

Abstract: Articles you may be interested in Improved thermal stability and electrical properties of atomic layer deposited HfO2/AlN high-k gate dielectric stacks on GaAs J. Vac. Sci. Technol. A 33, 01A136 (2015); 10.1116/1.4903367Electrical properties of thin zirconium and hafnium oxide high-k gate dielectrics grown by atomic layer deposition from cyclopentadienyl and ozone precursors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…The amount of nitrogen is expected to strongly influence the electrical properties, as demonstrated for Si and Ge MOS devices. [55][56][57][58][59][60] It was observed that nitrogen incorporation effectively improved the Si device property and reliability; however, excess nitrogen led to unfavorable interface charge and reduced mobility. [55][56][57][58][59] Regarding the Ge MOS device, low nitrogen contents reduced D it at the MOS interface, whereas excess nitrogen degraded the interface.…”
Section: -9mentioning
confidence: 99%
“…The amount of nitrogen is expected to strongly influence the electrical properties, as demonstrated for Si and Ge MOS devices. [55][56][57][58][59][60] It was observed that nitrogen incorporation effectively improved the Si device property and reliability; however, excess nitrogen led to unfavorable interface charge and reduced mobility. [55][56][57][58][59] Regarding the Ge MOS device, low nitrogen contents reduced D it at the MOS interface, whereas excess nitrogen degraded the interface.…”
Section: -9mentioning
confidence: 99%
“…The alkylamides of Ta and Nb have been used for the MOCVD of TaN and NbTaO (1– x ) N y . The Ta amides also have been used for ALD of Ta 2 O 5 and TaO x N y , but there have been only a couple of reports where metal amides of Ta were used for MOCVD of Ta 2 O 5 . To our knowledge, there has been no report solely on the MOCVD of Nb 2 O 5 using niobium alkylamides, apart from its application for growing NbTaO (1– x ) N y films by MOCVD .…”
Section: Introductionmentioning
confidence: 99%
“…The dielectric breakdown characteristics were also improved by in situ nitridation during ALD. Improved breakdown characteristics were also observed in the high-k film grown using lowtemperature N 2 /O 2 mixture plasma and NH 4 OH/H 2 O vapor [58,59]. The SIMS depth profiles in Figure 4.18 show that the C impurity concentration was reduced by the in situ NH 3 pulse.…”
Section: Reactants For In Situ N Incorporationmentioning
confidence: 85%
“…In addition, the nitrogen in the high-k film suppresses the leakage current density by passivating the electrical defects and improves the thermal stability, such as Si out-diffusion and crystallization temperature. The use of a reactant containing nitrogen, such as NH 3 , NH 4 OH, and low-temperature N 2 /O 2 mixture plasma enables to control the nitrogen profile in a high-k film without a high thermal budget and plasma damage during ALD growth [57][58][59][60]. On the other hand, the high thermal budget, serious plasma damage and excessive nitrogen incorporation at the interface by these postdeposition nitridation technique result in mobility degradation and impaired reliability [53,54].…”
Section: Reactants For In Situ N Incorporationmentioning
confidence: 99%